Strengthening organizational performance through accreditation research-a framework for twelve interrelated studies: the ACCREDIT project study protocol - Braithwaite, Jeffrey; Westbrook, Johanna; Johnston, Brian; Clark, Stephen; Brandon, Mark; Banks, Margaret; Hughes, Clifford; Greenfield, David; Pawsey, Marjorie; Corbett, Angus; Georgiou, Andrew; Callen, Joanne; et al. (BMC research notes, 2011)
Background Service accreditation is a structured process of recognising and promoting performance and adherence to standards. Typically, accreditation agencies either receive standards from an authorized body or develop new and upgrade existing standards through research and expert views. They then apply standards, criteria and performance indicators, testing their effects, and monitoring compliance with them. The accreditation process has been widely adopted. The international investments in accreditation are considerable. However, reliable evidence of its efficiency or effectiveness in achieving organizational improvements is sparse and the value of accreditation in cost-benefit terms has yet to be demonstrated. Although some evidence suggests that accreditation promotes the improvement and standardization of care, there have been calls to strengthen its research base. In response, the ACCREDIT ( A ccreditation C ollaborative for the C onduct of R esearch, E valuation and D esignated I nvestigations through T eamwork) project has been established to evaluate the effectiveness of Australian accreditation in achieving its goals. ACCREDIT is a partnership of key researchers, policymakers and agencies. Findings We present the framework for our studies in accreditation. Four specific aims of the ACCREDIT project, which will direct our findings, are to: (i) evaluate current accreditation processes; (ii) analyse the costs and benefits of accreditation; (iii) improve future accreditation via evidence; and (iv) develop and apply new standards of consumer involvement in accreditation. These will be addressed through 12 interrelated studies designed to examine specific issues identified as a high priority. Novel techniques, a mix of qualitative and quantitative methods, and randomized designs relevant for health-care research have been developed. These methods allow us to circumvent the fragmented and incommensurate findings that can be generated in small-scale, project-based studies. The overall approach for our research is a multi-level, multi-study design. Discussion The ACCREDIT project will examine the utility, reliability, relevance and cost effectiveness of differing forms of accreditation, focused on general practice, aged care and acute care settings in Australia. Empirically, there are potential research gains to be made by understanding accreditation and extending existing knowledge; theoretically, this design will facilitate a systems view of accreditation of benefit to the partnership, international research communities, and future accreditation designers. "Accreditation of health-care organisations is a multimillion dollar industry which shapes care in many countries. Recent reviews of research show little evidence that accreditation increases safety or improves quality. It's time we knew about the cost and value of accreditation and about its future direction." [Professor John Øvretveit, Karolinska Institute, Sweden, 7 October 2009]